Pelatihan Pembuatan Label Produk untuk Pemberdayaan UMKM Serbuk Jahe Merah Wangi di Desa Karang Indah Barito Kuala - Fitria; Anhar Khalid; Emy Iryanie (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The importance of labels for a community business is a visual representation of the brand identity and values it wants to convey to the community. Partners said that they had tried to market products outside the village and leave their products in several souvenir shops and minimarkets, but were rejected because they saw that the products offered were still very simple, especially when seen from their packaging, which was still traditional and did not have adequate labels. This made it difficult for their business to develop and be known to the outside market, so their sales were difficult to increase, and accompanied by this, the production process also did not develop. The methods used in this community service activity include lecture methods, practical methods, discussion methods, and, at the end, making a label and packaging design for partners. The results of this activity are maximising the use of technology for MSME partners as a means of introducing their products to a wider market so that partner products are better known in the market and easy to distinguish themselves from competitors who have similar products. This activity is considered very useful, making participants aware of the importance of good product labels and packaging that can support the sustainability of their businesses. After participating in this activity, they were also able to create their own label designs according to the wishes and needs of the products they had.